Development of Magnetic Particle Imaging (MPI) Scanner for Phantom Imaging of Tracer Agents - Irfan, M.; Dogan, N.; Dogan, O. Mercan; Bingolbali, A. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
This article presents the design and implementation of the magnetic particle imaging (MPI) scanner for phantom imaging of the potential tracer agents for MPI applications. The field-free point (FFP)-based spatial encoding of 4.3 T/m was implemented so that it helps to localize the superparamagnetic iron oxide nanoparticles (SPIONs) response inside the field of view (FOV). Solenoid drive coil and gradiometric receive coil were constructed to achieve 15 mT (peak amplitude) at 9.3 kHz. Moreover, a magnetic particle spectrometer (MPS) was utilized at 9.9 kHz for the characterization of relaxation time, frequency spectrum, and full-width at half-maximum (FWHM) of the particle signals in response to the excitation field at 9.9 kHz. The X-space algorithm was designed for the post-processing of the particle signals in the MPI scanner. Dextran-coated Perimag and carboxydextran-coated Vivotrax plus were characterized with MPS followed by the phantom imaging with MPI scanner. Perimag was found as fast relaxation sample (low relaxation time), narrow pulsewidth (high spatial resolution), and higher signal intensity compared to the Vivotrax plus.
Keywords: Imaging; Magnetic resonance imaging; Spatial resolution; Magnetic fields; Iron; Imaging phantoms; Image reconstruction; Field-free point (FFP); field of view (FOV); full-width at half-maximum (FWHM); magnetic particle imaging (MPI); magnetic particle spectrometer (MPS); superparamagnetic iron oxide nanoparticles (SPIONs); TRACKING; Engineering; Physics